Child Position Analysis As A Criminal Actor Of Homosexual In Juvenile Criminal Justice System - Cucuk Kristiono; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to formulate government policies in handling children who commit crimes through the Juvenile Criminal Justice System. This study uses a normative juridical method with a library study data collection method. The results of this study indicate that the formulation policy of the Garut Police Criminal Law enforcement through the Garut District Court Decision Number 10/Pen.Pid.Sus-Anak/2018/PN Grt against children as perpetrators of homosexual crimes turns out to be treated the same as children who commit other conventional crimes such as theft. , persecution, fights and others. The decision from the court is that rehabilitation should be carried out, the handling of which is only handed over to Islamic boarding schools, meaning that there is no special treatment in rehabilitating children who commit homosexual crimes. Whereas homosexual perpetrators are deviant behavior and must get special treatment especially if they are still children with the hope of recovering, of course it is greater in the form of integrated treatment not only from the spiritual aspect, there must be treatment from the medical and psychological aspects, so that the goals of rehabilitation will be more maximally achieved. . Suggestions related to the findings of this research is the need to include articles in Act No. 11 of 2012 to regulate more specifically in the implementation of the rehabilitation of children as perpetrators of homosexual crimes.